Peroxisome Proliferator-Activated Receptor α Reduces Endothelin-1-Caused Cardiomyocyte Hypertrophy by Inhibiting Nuclear Factor-κB and Adiponectin - Hsu-Lung Jen; Po-Len Liu; Yung-Hsiang Chen; Wei-Hsian Yin; Jaw-Wen Chen; Shing-Jong Lin (Hindawi Limited, 2016)
Peroxisome proliferator-activated receptor α (PPARα) plays a role in the pathogenesis of cardiac hypertrophy, although its underlying mechanism remains unclear. The purpose of this study was to evaluate the effect of PPARα activation on endothelin-1- (ET-1-) caused cardiomyocyte hypertrophy and explore its underlying mechanisms. Human cardiomyocytes (HCMs) were cultured with or without ET-1, whereafter the inhibitory effects of fenofibrate, a PPARα activator, on cell size and adiponectin protein were tested. We examined the activation of extracellular signal-regulated kinase (ERK) and p38 proteins caused by ET-1 and the inhibition of the ERK and p38 pathways on ET-1-induced cell size and adiponectin expression. Moreover, we investigated the interaction of PPARα with adiponectin and nuclear factor-κB (NF-κB) by electrophoretic mobility shift assays and coimmunoprecipitation. ET-1 treatment significantly increased cell size, suppressed PPARα expression, and enhanced the expression of adiponectin. Pretreatment with fenofibrate inhibited the increase in cell size and enhancement of adiponectin expression. ET-1 significantly activated the ERK and p38 pathways, whereas PD98059 and SB205380, respectively, inhibited them. Our results suggest that activated PPARα can decrease activation of adiponectin and NF-κB and inhibit ET-1-induced cardiomyocyte hypertrophy.